Obliteration - Murray, James S. (James Stephen), 1976-; Wearmouth, Darren (An awakened novel, 2020)
"Thanks to the heroics of former New York City Mayor Tom Cafferty and his team, the world is once again safe. The villainous Foundation for Human Advancement has been dismantled, the cities of the world are safe from nuclear annihilation, and Cafferty is now on a hunt to decimate every nest of creatures on the planet. When Cafferty enters a nest underneath the Nevada desert, he is horrified to find it completely empty. It can only mean one thing: the battle for survival is not over. Across the planet, creatures are emerging from their subterranean homes. Now, the all-out war against humanity has begun a war in which only one apex species will survive. Humankind has finally met its match."--Provided by publisher.